The Pacific Alliance, a threat to tobacco control? Analysis of an “under the radar” trade pact - Stella Bialous; Eric Crosbie (Tobacco Induced Diseases, 2018)
Background There has been robust debates about the impact of trade agreements, specifically the Trans-Pacific Partnership (TPP), on tobacco control. However, the potential impact on tobacco control of a multi-lateral trade agreement to increase trade in the Pacific region, the Pacific Alliance (PA), established in 2011 and with 52 observer countries, has not been discussed.